Fresh and preserved green fodder modify effects of urinary acidifiers on urine pH of horses. Issue 2 (30th March 2013) - Goren, G.; Fritz, J.; Dillitzer, N.; Hipp, B.; Kienzle, E.
Summary Hay stabilises urine pH in horses. It is unknown whether this is an effect of structure or of chemical composition. In this study, four ponies (230–384 kg body weight [BW]) were fed six different diets with either a structure or a composition similar to hay with and without acidifiers in a cross‐over experimental design in amounts to maintain body weight with the following main compounds: Fresh grass (GRASS), alfalfa hay (ALF), grass cobs (COBS), grass silage (SIL), straw (STR) or extruded straw (STRe) for 2 to 10 days. Urine pH was measured in all trials, blood pH, blood base excess and bicarbonate as well as mineral balance were determined in GRASS, ALF, STR and STRe. In the trials with straw and extruded straw, urine pH decreased significantly (STR control: 7.8 ± 0.23, acidifier: 5.2 ± 0.38) when acidifiers were added, whereas in all other diets that were based on fresh or preserved green fodder, pH did not decrease below 7. Blood pH was similarly affected by diet and acidifiers. Acidifiers had little effect on the pre‐prandial blood pH, only in diet STR there was a significant reduction in relation to control. Post‐prandial blood pH was significantly reduced by acidifiers in all diets. Blood bicarbonate and base excess showed corresponding effects. Faecal and renal mineral excretion and apparent mineral digestibility were not systematically affected by diet or acidifiers except for chloride. Chloride added as inorganic chloride salt had an even better apparent digestibility than chloride originating from feed. Because only green plant material stabilised acid base balance, chlorophyll and its metabolites are discussed as potential mediators of the effect of green fodder on acid base balance.